Efektivitas Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat dalam Rangka Pengendalian Penyebaran Covid-19 di Kota Bandung - Fajar Muhandari; Muhammad Ilham (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
For almost two years, all people throughout Indonesia and even in the world have lived side by side with the COVID-19 virus, including the city of Bandung, which is one of the districts/cities in Indonesia, with cases of the spread of COVID-19 continuing to increase. In order to break the chain of spread of COVID-19, the Bandung city government has made various policies, ranging from Large-Scale Social Restrictions to the policy of Enforcement of Restrictions on Emergency Community Activities. However, in its implementation, when the government tightened policies through the Enforcement of Restrictions on Emergency Community Activities, all people in the city of Bandung suffered material losses. And when the policy on the enforcement of restrictions on community activities was relaxed, there were more cases. To see the effectiveness of the policy of Enforcement of Restrictions on Community Activities in the City of Bandung in tackling the spread of COVID-19, it is necessary to have further coherent studies related to the impact of the policy on the community.